PENGEMBANGAN KARAKTER SOSIAL EMOSIONAL DENGAN PEMANFAATAN MEDIA BALOK WARNA-WARNI DAN BAHAN ALAM DI TK NEGERI 08 KOTA BIMA - Faridah; Daroe Iswatingsih; Nurul Arifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the development of children's social-emotional character through the use of colourful blocks and natural materials at State Kindergarten 08 in Bima City. The study used a qualitative field research approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the use of colourful blocks and natural materials can stimulate cooperation, empathy, responsibility, and emotional control in children. Children appear to be more active, communicative, and able to work together in groups through constructive play activities such as building a ‘friendly mini city’. Furthermore, the important role of teachers as mentors who guide and teach children to manage their emotions and instil positive social values through good and reflective interactions. This study concluded that State Kindergarten 08 in Bima City is able to facilitate children's learning with innovative media.